2006
DOI: 10.1111/j.1463-5224.2006.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for selected ophthalmic diagnostic tests of the ferret (Mustela putorius furo)

Abstract: Staphylococcus sp. and Corynebacterium sp. were isolated from healthy conjunctival and eyelid margins, suggesting they are normal constituents of the conjunctival flora of the ferret. Results for selected ocular diagnostic tests investigated here for the ferret eye were as follows: intraocular pressure: 14.50 +/- 3.27 mmHg; Schirmer tear test: 5.31 +/- 1.32 mm/min; central corneal thickness: 0.337 +/- 0.020 mm. No statistically significant differences between ages or genders were found for any of the results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
4
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
8
43
4
4
Order By: Relevance
“…The same have been reported in dogs, capybaras, and ferrets (Gelatt & MacKay 1998, Mughannam et al 2004, Montiani-Ferreira et al 2006.…”
Section: Discussionsupporting
confidence: 60%
“…The same have been reported in dogs, capybaras, and ferrets (Gelatt & MacKay 1998, Mughannam et al 2004, Montiani-Ferreira et al 2006.…”
Section: Discussionsupporting
confidence: 60%
“…In male ferrets it was 4.80±0.88mmHg and in females 5.72±1.50mmHg (Montiani-Ferreira et al 2006). Guinea pigs have measurements of 0.36±1.09mm/min and this low level is thought to be the result of not having reflex secretions due to the low corneal sensitivity or limited lacrimal reflex (Trost et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Average IOP levels of several species have been reported in the literature, including hedgehog (20.1±4.0mmHg) (Ghaffari et al 2011), goat (Capra hicus) (10.8±1.7mmHg) (Broadwater et al 2007), Sanjabi sheep (9.60±2.87mmHg LE, 9.15±2.36mmHg RE) (Ghaffari et al 2011), llama (Lama glama) and alpacas (Lama pacos) 16.55±3.55mmHg (Nuhsbaum et al 2000), rhinoceros (32mmHg) , capybara (16.47±4.28 mmHg) (Montiani-Ferreira et al 2008), ferret (14.5±3.2mmHg) (Montiani-Ferreira et al 2006), zebra (29.47±3.43mmHg), Arabian oryx (11.76±3.43mmHg) (Ofri et al 1998) and broad-snouted caiman (12.9±3.2mmHg) (Oriá et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have identified the resident microbiota of the conjunctiva and all showed the prevalence of Gram-positive, even in different animal species, such as dogs (Anvisa, 2013), horses, capybara, capuchin monkey, domestic ferret (Montiani-Ferreira et al, 2006;2008a;2008b) or even aquatic habitat animals as beavers, showed the same profile (Cullen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The main genus of microorganisms isolated in ophthalmic changes animals are Staphylococcus (Prado et al, 2005); Wang et al, 2008), followed by Streptococcus, Pseudomonas and Escherichia coli (Tolar et al, 2006) In dogs, Staphylococcus pseudintermedius is identified as the main agente (Montiani-Ferreira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%